THE IMPLEMENTATION OF LEARNING MANAGEMENT IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION FOR STUDENTS AT MTsN 2 LANGKAT - Sudirman Sudirman (UIN Sumatera Utara Medan, 2021)
Students need for qualified Islamic education is strongly influenced by the implementation of a systematic, programmed, and measurable learning management. This study aims to describe the implementation of learning management in improving the quality of Islamic education for students at MTsN 2 Langkat. This empirical study follows a qualitative approach with a descriptive-analytical study method. The data were collected through interviews, observation, and documentation analysis. The implementation of learning management can improve the quality of Islamic education for students at MTsN 2 Langkat. Improving the quality of education can be seen from the following aspects: (1) learning planning that involves all parties during the deliberation/meeting at the Madrasah, (2) the implementation of learning carried out in the Madrasah (inside and outside the classroom) as well as the tahfiz al-Qur'an program and the congregational Dhuha prayer; (3) learning supervision carried out systematically with academic and managerial supervision from the Ministry of Religion in the district and the Head of the Madrasah; (4) learning evaluation carried out in written, in worship practice and orally every semester.